2022
DOI: 10.1038/s41566-022-01010-1
|View full text |Cite
|
Sign up to set email alerts
|

Observation of light-driven band structure via multiband high-harmonic spectroscopy

Abstract: Intense light–matter interactions have revolutionized our ability to probe and manipulate quantum systems at sub-femtosecond timescales1, opening routes to the all-optical control of electronic currents in solids at petahertz rates2–7. Such control typically requires electric-field amplitudes in the range of almost volts per angstrom, when the voltage drop across a lattice site becomes comparable to the characteristic bandgap energies. In this regime, intense light–matter interaction induces notable modificati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…For short laser pulses, this happens already at intensities where the contribution of intraband currents due to ionization is not yet dominant. The mechanism is different from the influence of Bloch electron motion which has been observed before in HHG 10,11 because that is related to intraband currents, which are seeded by the irreversible (or real) population. Furthermore, the observed effect is in the realm of perturbative optics, because the iterative series 20 converges and reproduces the interference structure.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…For short laser pulses, this happens already at intensities where the contribution of intraband currents due to ionization is not yet dominant. The mechanism is different from the influence of Bloch electron motion which has been observed before in HHG 10,11 because that is related to intraband currents, which are seeded by the irreversible (or real) population. Furthermore, the observed effect is in the realm of perturbative optics, because the iterative series 20 converges and reproduces the interference structure.…”
mentioning
confidence: 62%
“…For terahertz fields it was found using a numerical switch-off analysis that Bloch oscillations contribute substantially to HHG 10 . Very recently, it has been reported that HHG produced by two-color fields exhibit phase variations that can be associated with reaching the zone edges 11 . On the other hand, the decoherence dynamics of strong-field processes in solids are disputed, with many recent calculations assuming the ultrafast loss of interband coherence with few-femtosecond dephasing times 7,[12][13][14][15] .…”
mentioning
confidence: 99%
“…For short laser pulses, this happens already at intensities where the contribution of intraband currents due to ionization is not yet dominant. The mechanism is different from the influence of Bloch electron motion on intraband currents (which are seeded by the irreversible or real population), which has been observed before in HHG [10,11]. The observed effect is in the realm of perturbative optics, because the iterative series [20] converges and reproduces the interference structure.…”
mentioning
confidence: 69%
“…For terahertz fields it was found using a numerical switch-off analysis that Bloch oscillations contribute substantially to HHG [10]. Very recently, it has been reported that HHG produced by two-color fields exhibit phase variations that can be associated with reaching the zone edges [11]. On the other hand, the decoherence dynamics of strong-field processes in solids are disputed, with many recent calculations assuming ultrafast loss of interband coherences with few-femtosecond dephasing times [7,[12][13][14][15].…”
mentioning
confidence: 99%
“…This scheme can be directly applied to laser-driven solids where the band structure can be transiently modified 48,49 within the optical cycle. In such systems, the multiple band structure, dressed by the laser field, defines several competing quantum paths, which are all coherently mapped onto the transient absorption spectrum.…”
mentioning
confidence: 99%